2007
DOI: 10.1176/appi.ps.58.10.1317
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Antidepressant Treatment Preceding Suicide in a Medicaid Population

Abstract: Although there are several other potential explanations, the study findings provide indirect evidence that there is underdiagnosis or undertreatment of African Americans with serious mood disorders. Further research on this question in African-American populations is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…Asians not only were much less likely to receive a diagnosis of depression but when diagnosed, were 55% less likely than non-Hispanic whites to receive a medication to treat this condition. In contrast with findings from a decade ago, we found no significant differences in use of psychotropic drugs across racial/ethnic groups with schizophrenia and other psychosis 11, 32, 33 . One reason for this difference may be that the previous studies focused on patients from the Veterans Health Administration 7, 11, 34 or Medicaid 19, 35, 36 which tend to serve the most disadvantaged patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Asians not only were much less likely to receive a diagnosis of depression but when diagnosed, were 55% less likely than non-Hispanic whites to receive a medication to treat this condition. In contrast with findings from a decade ago, we found no significant differences in use of psychotropic drugs across racial/ethnic groups with schizophrenia and other psychosis 11, 32, 33 . One reason for this difference may be that the previous studies focused on patients from the Veterans Health Administration 7, 11, 34 or Medicaid 19, 35, 36 which tend to serve the most disadvantaged patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Our expectation of relative underdocumentation of comorbidity on the death certificates of the minority suicides is partially supported by a records-based study [ 11 ]. Subjects were adult enrollees in TennCare, Tennessee's Medicaid-waiver managed care program, a public assistance program which offers equal financial access to all low-income groups [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subjects were adult enrollees in TennCare, Tennessee's Medicaid-waiver managed care program, a public assistance program which offers equal financial access to all low-income groups [ 12 ]. This study found that only 29% of African-American suicides and possible suicides, as compared to 51% of white opposites, used prescribed antidepressants in the year prior to their deaths [ 11 ]. The authors interpreted this differential as indirect evidence that serious mood disorders are underdiagnosed or undertreated in African-Americans.…”
Section: Introductionmentioning
confidence: 99%
“…Although confined to Blacks and Whites (Hispanics not independently presented), data from a Tennessee records-based study addressed discrepant documentation of psychiatric comorbidity between US minority and White suicides [23]. Subjects were adult enrollees in TennCare, Tennessee's Medicaid-waiver managed-care program, which is intended to offer equal financial access to all low-income groups.…”
Section: Introductionmentioning
confidence: 99%